Giant GIST of the stomach: a successful case of safe resection with preoperative simulation using three-dimensional CT angiography. Issue 7 (February 2018) - Matsuo, Kentaro; Inoue, Masaya; Shirai, Yasutsugu; Kataoka, Tatsuki; Kagota, Shuji; Taniguchi, Kohei; Lee, Sang-Woong; Uchiyama, Kazuhisa
Abstract: Rationale: We report a very rare case of safely resectable giant gastrointestinal stromal tumor (GIST) with preoperative three-dimensional computed tomography (3D-CT) angiography in spite of no neoadjuvant treatment. Patient's concern: A 71-year-old woman presented to our hospital with an abdominal giant tumor. As this giant tumor could not be accurately diagnosed by preoperative investigation, we had to perform her surgical treatment without neoadjuvant treatment. However, preoperative 3D-CT angiography clearly showed that the tumor was supplied by the right gastroepiploic artery (RGA). Based on the preoperative information, a surgical procedure was undertaken. Diagnosis: Giant tumor of stomach with suspicion of GIST. Interventions: Laparotomy guided by 3D-CT imaging including angiography. Outcome: The giant tumor originated from the greater curvature of the distal stomach and was supplied by the RGA, as expected. The tumor was resected easily under the accurate preoperative anatomical information. The tumor measured 20 cm × 20 cm in size and weighed 2500 g (Fig. 2C and D). Histopathological examination showed evidence of growth of spindle-shaped cells and a low mitotic index (3 per 50 high-power field, Fig. 3B). Immunohistochemical examination showed positive immunoreactions for KIT, CD34, and DOG1 (Fig. 3 C–E), but negative ones for SMA and S-100 protein (Fig. 3F and G). Consequently, we made a final diagnosis of an extra luminal GIST of the stomach. The post-operative course was uneventful, and so the patient was discharged on postoperative day 13. Lessons: Making full use of an imaging procedure such as 3D-CT angiography is one of the effective tools for the surgical management of giant-size tumors including giant GISTs.